Free for All: Foods, Landscapes, and Lives in the Paraguayan Chaco - Wyndham, Felice S. (Ethnobiology Letters, 2016)
Foods and foodscapes structure and inform our experiences as ethnobiologists and ethnographers, the way we interact with and learn from teachers in study sites, and how relations between peoples and between people and landscapes unfold over time. This short memoir essay revisits my education in foodscapes with the Ayoreo community of Jesudi in the Paraguayan Chaco through stories and experiences of food procurement and distribution. From landscapes in which food was free for all (non-monetized) to contemporary encroachments and land-grabbing in the Chaco for globally-connected markets, the transformations have been rapid and witnessed by Ayoreo and other dispossessed indigenous groups.